1986
DOI: 10.1111/j.1699-0463.1986.tb02961.x
|View full text |Cite
|
Sign up to set email alerts
|

Cystosarcoma Phyllodes

Abstract: The clinico‐pathological aspects of 19 cases of cystosarcoma phyllodes (CP) were reviewed with special attention to the occurrence of associated breast carcinoma (BC). Twelve women had histologically benign, 4 had borderline and 3 malignant CP. Recurrent CP was diagnosed in 9 women within 1 to 15 years after initial treatment. Of the 19 women, 5 had associated in situ or invasive BC, 2 with the primary CP and 3 with its recurrences. In 1 case the BC was located within the confines of the CP, whereas in 4 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Ninety-eight cases of in situ or invasive carcinoma within a PT were identified in the literature [3‒64], including 31 cases compiled from case series by Sin et al, Widya et al, Co M. et al, Saimura et al, and Nistor-Ciurba et al [65‒69], as shown in Table 1. Patients averaged 49 years old, ranging from 19 to 80 years.…”
Section: Resultsmentioning
confidence: 99%
“…Ninety-eight cases of in situ or invasive carcinoma within a PT were identified in the literature [3‒64], including 31 cases compiled from case series by Sin et al, Widya et al, Co M. et al, Saimura et al, and Nistor-Ciurba et al [65‒69], as shown in Table 1. Patients averaged 49 years old, ranging from 19 to 80 years.…”
Section: Resultsmentioning
confidence: 99%